Exergames: proposal for a gamepad to sense player movements - Herrera del Gener, Aldana Mariel (2023)
Exergames are a good alternative to perform physical activity while being entertained with a video game. This paper reviews the history of exergames with walkin-place mechanisms for locomotion, and presents the development of a prototype video game controller (gamepad) with functionalities to sense the player's movements (walk, run, and jump). Then, an exergame that was implemented and integrated with the controller is described. This proposal was evaluated by users considering usability and user experience analysis. The results obtained allow affirming that the gamepad integrated with the video game were positively valued by the participants during the test sessions and allowed the realization of physical activity while maintaining entertainment through the game.